(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The physical culture of the community members of a healthy lifestyle (STT) and special knowledge related to it is carried out mainly through the existing directions of the physical education process – general physical training (UJT), Professional Physical Training (KHJT), "sports training" and "mass volunteer sports" (Oks).